**Weegy:** The following system of equations is A. independent

**User:** Solve the following system by graphing.
x - y = 4
x + y = 2
What is the solution of the system?

**Weegy:** The solution set of (3x - 1)^2 = 5 is x = x = (5^1/2)/3 + 1/3 . (3x - 1)^2 = 5 3x - 1 = 5^1/2 3x = 5^1/2 + 1 x = (5^1/2)/3 + 1/3

**User:** Solve the following system by graphing.
x + y - 6 = 0
x - y = 0
What is the solution of the system?

**User:** y = 2x + 3
2y = 4x + 6
The system of equations has _____ solution(s).

**User:** For the following system, use the second equation to make a substitution for y in the first equation.
2x + y = 6
y = 3x + 4
What is the resulting equation?

**User:** For the following system, use the second equation to make a substitution for y in the first equation.
3x + y = 1
y + 4 = 5x
What is the resulting equation?

**User:** For the following system, use the second equation to make a substitution for x in the first equation.
x + 5y - 10 = 0
x = 2y - 8
What is the resulting equation in simplest form?

(More)8

x - y = 4

x + y = 2

adding up equations the result is 2x = 6

x = 6/2 = 3

3 - y = 4

y = 3 - 4 = -1

the solution for the system x - y = 4 x + y = 2 is (3, -1)

Added 5/8/2015 2:54:53 AM

This answer has been confirmed as correct and helpful.

Confirmed by

sujaysen [5/8/2015 10:21:08 AM]

8

y = 2x + 3

2y = 4x + 6

substitute y in the second equation the result is:

2(2x + 3) = 4x + 6

4x + 6 = 4x + 6

4x - 4x = 6 - 6

0 = 0

the system of equations y = 2x + 3 2y = 4x + 6 has infinite solutions.

Added 5/8/2015 2:56:06 AM

This answer has been confirmed as correct and helpful.

Confirmed by

sujaysen [5/8/2015 10:23:40 AM]

8

For the system 3x + y = 1 y + 4 = 5x, use the second equation to make a substitution for y in the first equation, the resulting equation is 3x + (5x - 4) = 1.

Added 5/8/2015 2:58:26 AM

This answer has been confirmed as correct and helpful.

8

For the following system, x + 5y - 10 = 0 x = 2y - 8, use the second equation to make a substitution for x in the first equation. The resulting equation is: 2y - 8 + 5y - 10 = 0, it is 7y - 18 = 0 in simplest form.

Added 5/8/2015 2:59:53 AM

This answer has been confirmed as correct and helpful.